2018
DOI: 10.31086/tjgeri.2018240412
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of the Status of Emergency Department use by Elderly Patients and of the Indicators for Ambulance Use

Abstract: Turkish Journal of Geriatrics (TJG) is welcoming you with its new face in the first issue of 2018. Our scientific journey has started in 1998 and since then, our efforts specifically targeted to improve health and wellbeing of aging societies globally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…We suspect that this rate would further increase if the age limit is increased, because our region is located at the border, thus providing more opportunities for truck drivers. Yenal et al (18) reported that 34.2% of the elderly patients were admitted to the emergency department through an ambulance; this rate was22.2% in our study. We think this low rate is related to the low injury severity in these cases.…”
Section: Discussionsupporting
confidence: 44%
“…We suspect that this rate would further increase if the age limit is increased, because our region is located at the border, thus providing more opportunities for truck drivers. Yenal et al (18) reported that 34.2% of the elderly patients were admitted to the emergency department through an ambulance; this rate was22.2% in our study. We think this low rate is related to the low injury severity in these cases.…”
Section: Discussionsupporting
confidence: 44%
“…Compared to other studies evaluating emergency department admissions and ambulance calls of elderly patients in our country, the population is older, but the gender distribution is similar [9,10,11]. In Turkey, in 2019 women constitutes 55.8% of the elderly population and gender life expectancy is longer than men 3 . The reason for this difference among gender may be that we only evaluated the elderly population in this study.…”
Section: Discussionmentioning
confidence: 64%
“…In the USA, elderly patients account for more than 15% of all emergency department (ED) patients 1 . However, in Turkey, 20% of patients attending the ED are patients aged 65 years and older [1,2], and 34.2% of elderly patients arrive at the ED by ambulance [3]. In particular, the number of patients aged 80 years and older who are transferred by ambulance is higher than that of all other age groups [4].…”
Section: Introductionmentioning
confidence: 99%
“…The growth in the absolute numbers of persons 65 years of age and older will potentially lead to an increase in the emergency department (ED) visits rates [5][6][7][8] . This tendency represents a significant challenge for the ED in the context of resource scarcity and restricted specific critical skills of emergency healthcare workers in caring for this population [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%